Nghiên cứu sự tạo thành gốc tự do OH* từ H2O2 và khả năng oxi hóa của chúng trong hệ xúc tác Co2+ + xitric axit (H4L) bằng phương pháp dùng các chất ức chế. - Dưỡng và cộng sự, Nguyễn Văn (Vietnam Journal of Chemistry, 2014)
By method of using inhibitors in order to study the catalytic oxidation process of indigocarmine (Ind) taking place according to the OH* radical chain mechanism. This study was performed in the systems: H2O - Co2+ -H4L - Ind - Ac -H2O2 (1) H2O - Co2+ -H4L - Ind - Hq -H2O2 (2) H2O - Co2+ -H4L - Ind - Pa -H2O2 (3) This article presents our results of calculating the rate constant k(Ind + OH*) of oxidizing Indigocarmine by hydroxyl radicals OH* with the help of Turbo Pascal programming languages.